A structurally versatile nickel phosphite acting as a robust bifunctional electrocatalyst for overall water splitting. Issue 5 (22nd March 2018) - Menezes, Prashanth W.; Panda, Chakadola; Loos, Stefan; Bunschei-Bruns, Florian; Walter, Carsten; Schwarze, Michael; Deng, Xiaohui; Dau, Holger; Driess, Matthias
Abstract : The mechanistically distinct and synergistic role of phosphite anions in hydrogen evolution and nickel cations in oxygen evolution have been uncovered for active and durable overall water splitting catalysis in nickel phosphite. Abstract : The design and development of economical and highly efficient electrocatalysts for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) under alkaline conditions are vital in lowering the overall energy losses in alkaline water electrolysis. Here we present a nickel phosphite, Ni11 (HPO3 )8 (OH)6, belonging to the unique class of phosphorus-based inorganic materials with striking structural features that have been explored for the first time in the reaction of electrocatalytic overall water splitting with a profound understanding of the system using in situ and ex situ techniques. When electrophoretically deposited, the nickel phosphite exhibited remarkable electrocatalytic activity, yielding considerably low overpotentials for both the OER and HER with extreme structural stability and enhanced durability in alkaline media. Apart from the attractive structural merits, the higher activity of nickel phosphite is mainly attributed to the formation of oxidized nickel species in the catalytic OER process, while subtle experimental evidence of the participation of phosphite anions for the acceleration of the HER with the support of Ni 2+ cations as catalytically active sites is identified, which is highly compelling and has never been previously discovered. Finally, the bifunctionality of nickel phosphite was demonstrated by constructing an alkaline water electrolyzer with a low cell voltage and over 4 days of undiminishing stability. This work offers an appealing cost-effective system based on earth-abundant metals for water electrolysis and can be extended to other transition metal based homo- or hetero-bimetallic phosphites.